Studies on Some Metal Complexes of 4-Formyloxime-1,3- Diphenyl-2-Pyrazolin-5-one - J. Kharodawala, Mohammad; K. Rana, Arjun (Asian Journal of Chemistry, 2010)
Chelates of VO(II), Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II) and Zn(II) with 4-formyloxime-1,3-diphenyl-2-pyrazolin-5-one (FDPPZ) have been prepared and characterized on the basis of elemental analysis, conductivity, magnetic moment and spectral studies. The IR spectra suggest that the ligand shows bidentate behaviour. All chelates except Cr(lll), Fe(III) and VO(II) have the general composition M(FDPPZ)2·2H2O, while Cr(III) and Fe(III) chelates have M(FDPPZ)3 composition. The VO(II) chelates have VO(FDPPZ)2·H2O composition. The ligand field parameters for VO(II). Cr(III), Co(II) and Ni(II) chelates are also calculated.